Dulamayo Barat Village Community Empowerment in Agroforestry System Development - Dewa Oka Suparwata; Merita Ayu Indranti; Moh. Muchlis Djibran; Meity Mokoginta; Taufik Jarot Andrayanto (Journal of Universal Community Empowerment Provision, 2021)
Nowadays, land management requires a paradigm recondition towards wise behavior in utilizing natural resources. An alternative that can be consistently applied to support this is the application of agroforestry patterns. The purpose of this service is to provide counseling, training, and assistance to the community in agroforestry development. This activity was carried out in Dulamayo Barat Village, Telaga District, Gorontalo Regency. The method used is focused discussion and group training. The procedural activities are divided into three stages, namely planning (observation and socialization), implementation (counseling, training, and fostering productive activities), and evaluation stages (reviewing the participation of agroforestry developing communities). The results obtained in this service activity are: (a) observation activities describing the existence of forest destruction, monoculture patterns, cultivation without land cover, and low socio-economic aspects; (b) socialization is carried out to the village government to establish cooperation and request support in community empowerment; (c) extension is carried out by providing material on the prospects for agroforestry development; (d) the training content provides reinforcement for the community to choose a combination pattern of agroforestry and top grafting; and (e) the evaluation phase shows that 60% of the community participated in planning-implementation, and 47% participated in the evaluation of the agroforestry program.